Rheological properties of concentrated aqueous fluorapatite suspensions - Albano, Maria Patricia (2010)
The Ca3(PO4)2 and CaF2 powders were mixed in a 3:1.5 ratio, calcined at 1000 ºC and then milled in an aqueous media with the pH initially adjusted at 9. The resulting powder had a Ca/P atomic ratio of 1.67, which corresponded to the theoretical composition of fluorapatite (FA), Ca10(PO4)6F2. Its reactivity in an aqueous solution having two initial pH values with a concentration of ammonium polyacrylate (NH4PA) was  investigated as a function of time. The adsorption behaviour of NH4PA and the influence of NH4PA addition on the rheological properties of 40 vol.% FA slips were studied. In addition, the influence of the volume fraction of solids on the rheological behaviour of stabilized FA slips was determined. Finally, the effect of poly(vinyl)alcohol (PVA) addition on the relative viscosity of 38 vol.% FA suspensions stabilized with NH4PA was investigated. The dissolution of FA was enhanced by decreasing the pH to an acidic value; the increase in pH above 7 markedly reduced the Ca2+/H+ exchange reaction rate. As a result, well-stabilized aqueous suspensions could be obtained at pH close to 9 in a wide range of solids  loading. The minimum viscosity of 40 vol.% slips at pH 8.9 occurred at 0.6 wt% of NH4PA. An important increase in the yield stress was  observed for suspensions with a volume fraction of solids higher than about 46 vol.%. The addition of 0.5–1 wt% PVA to a well-stabilized FA slip caused aggregation of particles by a depletion flocculation mechanism, thereby increasing the slip viscosity.